Corporal Punishment in Childhood Interfaces with Happiness in Adulthood - Navaitis, Gediminas; Kairienė, Brigita; Gaidys, Vladas (Pedagogika, 2015)
There are enough provisions in the Lithuanian legislation prohibiting the imposition of corporal punishment, however, legal restrictions are ineffective – Lithuania is identified as the country in which parents often impose corporal punishment on their children. Although the harm of corporal punishment has been established, however, the debate that parents must be able to use corporal punishment as a dissuasive measure has been continuing up till now. Certain countries have placed a legal ban on the use of corporal punishment, and that has contributed to the change of the attitude of society towards the child. The article attempts to find still new arguments that the ban of corporal punishment towards children would be forbidden by law in Lithuania. The goal of the study is to elicit views on the use of corporal punishment towards children, reveal the links of this view with the level of happiness and the experience of corporal punishment in childhood. The method of the study is a questionnaire survey at the respondent’s home. 1002 people that are older than 18 from 19 towns and 31 villages participated in the study. The study has established that the persons who underwent corporal punishment in childhood more often support the view that “moderate corporal punishment is a proper parenting tool” than those who did not undergo corporal punishment in childhood. It has come to light that the opinion of the Lithuanian society on the use of corporal punishment towards children is changing – the investigates, who belonged to the younger age groups assessed corporal punishment more negatively than the older investigates. The respondents with higher levels of education supported corporal punishment of children more rarely than the respondents with lower levels of education. It has been established that that those who underwent corporal punishment in their childhood feel less happy that those who did not undergo corporal punishment.